(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2025)
This contribution aims to investigate the diverse uses of imagery within the epic-chivalric genre. Through close textual analysis, it is evident that the employment of zoological similes related to deer hunting can be categorized into two distinct areas. In the erotic sphere, this topos is often associated with female figures, embodying either the wounded lover or the fleeing beloved pursued by hounds. Conversely, in the military context, the symbol portrays a collective entity (one of the warring armies) as vulnerable prey, depicted as a doe fleeing from a lion (the enemy leader) who has slain its cubs. This study demonstrates not only the presence of recurring thematic and symbolic patterns within the genre but also the often problematic interplay between the two key elements of 16th-century epic-chivalric poems: arms and love.